Arginine-Modified Polymers Facilitate Poly (Lactide-Co-Glycolide)-Based Nanoparticle Gene Delivery to Primary Human Astrocytes - Proulx, Jessica (Int J Nanomedicine, 2020)
PURPOSE: Astrocyte dysfunction is a hallmark of central nervous system injury or infection. As a primary contributor to neurodegeneration, astrocytes are an ideal therapeutic target to combat neurodegenerative conditions. Gene therapy has arisen as an innovative technique that provides excellent prospect for disease intervention. Poly (lactide-co-glycolide) (PLGA) and polyethylenimine (PEI) are polymeric nanoparticles commonly used in gene delivery, each manifesting their own set of advantages and disadvantages. As a clinically approved polymer by the Federal Drug Administration, well characterized for its biodegradability and biocompatibility, PLGA-based nanoparticles (PLGA-NPs) are appealing for translational gene delivery systems. However, our investigations revealed PLGA-NPs were ineffective at facilitating exogenous gene expression in primary human astrocytes, despite their success in other cell lines. Furthermore, PEI polymers illustrate high delivery efficiency but induce cytotoxicity. The purpose of this study is to develop viable and biocompatible NPsystem for astrocyte-targeted gene therapy. MATERIALS AND METHODS: Successful gene expression by PLGA-NPs alone or in combination with arginine-modified PEI polymers (A(n)P(n)) was assessed by a luciferase reporter gene encapsulated in PLGA-NPs. Cytoplasmic release and nuclear localization of DNA were investigated using fluorescent confocal imaging with YOYO-labeled plasmid DNA (pDNA). NP-mediated cytotoxicity was assessed via lactate dehydrogenase in primary human astrocytes and neurons. RESULTS: Confocal imaging of YOYO-labeled pDNA confirmed PLGA-NPs delivered pDNA to the cytoplasm in a dose and time-dependent manner. However, co-staining revealed pDNA delivered by PLGA-NPs did not localize to the nucleus. The addition of A(n)P(n) significantly improved nuclear localization of pDNA and successfully achieved gene expression in primary human astrocytes. Moreover, these formulations were biocompatible with both astrocytes and neurons. CONCLUSION: By co-transfecting two polymeric NPs, we developed an improved system for gene delivery and expression in primary human astrocytes. These findings provide a basis for a biocompatible and clinically translatable method to regulate astrocyte function during neurodegenerative diseases and disorders.